Development of the C-band radiometer and use it for sea surface temperature research in Vietnam - Lan Anh, Vo Thi; Ngoc, Ngo Tuan; Chung, Doan Minh; Kostov, K. G.; Vichev, B. I. (Communications in Physics, 2015)
The microwave (MW) sensors are being used widely on the ground based, airborne and satellite due to their advantage of being worked day/night and cloudy free. The MW radiometer (RDM) is an example of such passive MW device for remote measurement of environmental parameters as like soil moisture, sea surface temperatures. The satellite SMOS of ESA observing soil moisture and ocean salinity and satellite HYDROS of NASA are two examples of these devices. This paper describes briefly the research method and some results based on the protocol cooperative project between Vietnam and Bulgarian namely "Development of the C band radiometer and use it for vegetation biomass and sea surface temperature research in Viet Nam" accomplished by the Space Technology Institute.